Performance analysis of a nonlinear energy harvester with subharmonic responses based on discrete Meyer wavelet filtering scheme - Ribeiro, Mauricio A.; Varanis, Marcus; Tusset, Angelo M.; Machado, Raphaela C. [UNESP]; Litak, Grzegorz; Bathazar, J. M. [UNESP] (Springer Nature, 2024)
In this study, we investigate the nonlinear dynamics of a kinetic energy harvester featuring a single degree-of-freedom magneto-piezoelectric harvester with a double-well potential resonator. A detailed analysis of the simulation results revealed the influence of initial conditions on the average power output as we varied the frequency of the external force, noting the emergence of coexisting solutions. We identified three initial conditions corresponding to regions with distinct power outputs and analyzed the relationship between average power and system dynamics. Our findings showed that at higher excitation frequencies, inherent subharmonics emerged due to the multi-stable potential. By applying the discrete Meyer wavelet transform for signal processing, the filtered output signal retained approximately 93% of the original signal’s power with the subharmonics, closely matching the optimal frequency response. Wavelet filtering allows for a clearer identification of subharmonics, which plays a crucial role in optimizing performance.
Keywords: Double-well potential resonators; Energy harvesting; Nonlinear dynamics; Wavelet filtering